Understanding the Influence of Parasocial Interaction on Beauty Products Purchase Intention - Raquel Reis SOARES; Madalena CORREIA (Communications of International Proceedings, 2021)
Influencer marketing is a marketing approach, which may be mutually beneficial for influencers and brands. However, for this marketing strategy to be successful, it is critical that brands are aware of the characteristics that consumers value the most in digital influencers, allowing them to associate with the right digital influencer, thus investing in an appropriate strategy. The present study aimed to understand the impact of parasocial interaction has on purchase intention. An experimental method was developed, and a questionnaire was conducted with a sample size of 303 young Portuguese respondents. The findings suggested that parasocial interaction impact consumers' purchase intention when they are exposed to a low-involvement product. These findings offer relevant theoretical and practical implications for influencer marketing, especially for the beauty sector.
Keywords: Social Media Influencers; Parasocial Interaction; Product Involvement; Purchase Intention; Instagram.